Sensitivity Analysis of Real-Time Locational Marginal Price to SCADA Sensor Data Corruption - Choi, Dae-Hyun; Xie, Le (IEEE transactions on power systems, 2014)
This paper examines the impact of supervisory control and data acquisition (SCADA) data corruption on real-time locational marginal price (LMP) in electricity markets. We present an analytical framework to quantify LMP sensitivity with respect to changes in sensor data. This framework consists of a unified LMP sensitivity matrix subject to sensor data corruption. This sensitivity matrix reflects a coupling among the sensor data, an estimation of the power system states, and the real-time LMP. The proposed framework offers system operators an online tool to: 1) quantify the impact of corrupted data at any sensor on LMP variations at any bus; 2) identify buses with LMPs highly sensitive to data corruption; and 3) find sensors that impact LMP changes significantly and influentially. It also allows system operators to evaluate the impact of SCADA data accuracy on real-time LMP. The results of the proposed sensitivity based analysis are illustrated and verified with IEEE 14-bus and 118-bus systems with both Ex-ante and Ex-post real-time pricing models.